Lattice-Based Proxy Signature - Yali Jiang; Fanyu Kong; Xiuling Ju (2010 International Conference on Computational Intelligence and Security, 2010)
Those existing proxy signature schemes are mainly based on the assumed hardness of Big Integer Factoring problem and Discrete Logarithm problem. So they can't resist quantum attacks. This proxy signature scheme is based on the assumed hardness of some lattice problem, which can resist quantum attack. The key pair of proxy signer was generated using basis delegation technology. Combined with GPV basic signature scheme, the proxy signature scheme was constructed. This scheme is satisfied with all the security property of proxy signature schemes. Based on this scheme, variant lattice-based proxy signature schemes will be designed, such as blind proxy signature, multi-grade proxy signature, and identity-based proxy signature etc.